Measuring and Assessing the Success of Quality Improvement Strategies for Basic Education Institutions - Rizka Zusanti Siregar; Indra Sugianto; Mariono Mariono; Lesmana Ginting; Latifah Latifah; Erlina Anriani Siahaan (Universitas Pahlawan Tuanku Tambusai, 2023)
Quality of the school system is an important consideration for parents when homeschooling children. The research aims to measure and assess the success of the strategy to improve the quality of basic education institutions at the SD/MI level. The focus of the research is the analysis of indicators for measuring and assessing success as well as the level of strategy in the organization as an effort to improve the quality of basic education institutions. This research uses a qualitative approach with the method of literature study. The data sources and materials for analysis of the study use scientific literature in the form of books, articles, seminar proceedings (national or international), and final assignments (thesis, thesis, dissertation). Furthermore, the validity of the data was tested by cross-checking the study analysis materials. The results of this study concluded that the measurement and assessment of the level of success is based on learning components, including learning methods, learning facilities, and achieving goals. Furthermore, measurement and assessment efforts must be carried out with a periodic assessment system through indicators contained in the implementation operational standards (SOP). Finally, it is said that the quality of basic education institutions can be improved after using a tiered measurement and assessment strategy, starting from the assessment of the leadership level, the level of allied subject teachers (Subject Teacher Consultations), and for each subject teacher (subject).